Saturation with fluids of earthquake focal zones of Eurasian folded belt (according to 2D-3D inversion of MT data) - Belyavskiy, V. V. (Geofizicheskiy Zhurnal, 2012)
The information received at realization 2D-3D of inversion magnetotelluric the data, has allowed to estimate together with seismic constructions a mineralization and fluid-filled focal zones of earthquakes within the limits of Northern Caucasus and Тien-Shans, Pamirs, Altai-Sajns, Кorak- Kamchatkas regions. It is shown, that fluid-filled depends on character of seismicity and changes from the tenth shares up to the first interests.